Impacts of Heat Stress on Rabbit Immune Function, Endocrine, Blood Biochemical Changes, Antioxidant Capacity and Production Performance, and the Potential Mitigation Strategies of Nutritional Intervention - Liang, Zi-Long; Chen, Fan; Park, Sungkwon; Balasubramanian, Balamuralikrishnan; Liu, Wen-Chao (Frontiers in Veterinary Science, 2022)
Heat stress has become a widespread concern in the world, which is one of the major environmental stressors and causes substantial economic loss in the rabbit industry. Heat stress leads to multiple damages to the health of rabbits, such as organ damage, oxidative stress, disordered endocrine regulation, suppressed immune function and reproductive disorders, ultimately, induces the decreased production performance and increased mortality. Nutritional approaches, including feeding strategies, adjusting feed formula, and supplementing vitamins, minerals, electrolytes, Chinese herbal medicines, and functional active substances to the feed, were reported to mitigate the detrimental effects of heat stress in rabbits. Therefore, elucidating the damage of heat stress to rabbits; proper management and nutritional approaches should be considered to solve the heat stress issue in rabbits. This review highlights the scientific evidence regarding the effects of heat stress on rabbit’s immune function, endocrine, blood biochemical changes, antioxidant capacity and production performance, and the potential mitigation strategies of nutritional intervention to alleviate heat stress in rabbits; which could contribute to develop nutritional strategies in relieving heat stress of rabbits.